Evaluasi Kualitas dan Kuantitas Lumpur Alum dari Instalasi Pengolahan Air Minum Citayam - Adityosulindro, Sandyanto; Rochmatia, Nurul Hasanah; Hartono, Djoko Mulyo; Moersidik, Setyo Sarwanto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2020)
ABSTRACTWater treatment plants (WTPs) produces residues in the form of alum sludge during the treatment process. In Indonesia, due to various techno-economic constraints, some WTPs are not equipped by sludge treatment systems, so the generated alum sludge is discharged directly into water bodies without appropriate treatment. This condition may pollute water bodies because alum sludge contains various contaminants such as solid particles, organic compounds, inorganic metals, aluminum, and pathogenic microorganisms. This study aims to evaluate the characteristics of alum sludge from aspects of quality and quantity, which is indispensable for the design of sludge treatment facilities. Citayam WTP (capacity of 120 L/s) in Depok City was chosen as a case study. The study was conducted in several stages as follows: (i) survey and sampling; (ii) quality analysis of alum sludge; (iii) estimation of sludge generation; and (iv) mass and volume balance analysis. Results of comparative analysis of alum sludge quality against the Regulation of Minister of Environment of Indonesia 5/2014 shows alum sludge from flocculation units meets quality standards.Ã‚Â In contrast, alum sludge from sedimentation and filter units were exceeded for TSS, COD, and Total Coliform parameters. Quantity-wise, the estimation of sludge generation by theoretical and empirical methods was found to be 1,898 kg/day and 4,854 kg/day. Analysis of mass and volume balance using STAN software indicates that the theoretical approach is quite representative, while the empirical method tends to be over-estimated.Keywords: alum sludge, sludge quality, sludge generation, water treatment plant, case studyABSTRAKInstalasi pengolahan air (IPA)Ã‚Â dalam proses pengolahannya akan menghasilkan residu berupa lumpur alum. Di Indonesia, akibat berbagai kendala tekno-ekonomis, masih terdapat IPA yang belum memiliki sistem pengolahan lumpur alum sehingga langsung dibuang ke badan air tanpa pengolahan. Kondisi ini berpotensi mencemari badan air karena lumpur alum mengandung berbagai kontaminan seperti partikel padat, senyawa organik, inorganik, logam aluminiumÃ‚Â serta mikroorganisme patogen. Penelitian ini bertujuan untuk mengevaluasi karakteristik lumpur alum dari aspek kualitas dan kuantitas yang merupakan informasi penting dalam perancangan sistem pengolahan lumpur. IPA Citayam (Kapasitas 120 L/detik) di Kota Depok dipilih sebagai objek studi. Penelitian dilakukan dalam beberapa tahapan yakni survei dan sampling, analisis kualitas lumpur alum, estimasi timbulan lumpur, dan analisis neraca massa dan volume. Hasil perbandingan analisis kualitas lumpur alum terhadap PermenLH 5/2014 menunjukan lumpur alum dari unit flokulasi memenuhi baku mutu sedangkan lumpur alum dari unit sedimentasi dan filter melebihi baku mutu lingkungan untuk parameter TSS, COD dan Total Koliform. Dari aspek kuantitas, estimasi timbulan lumpur yang dilakukan dengan metode teoritik dan empirik berturut-turut sebesar 1.898 kg/hari dan 4.854 kg/hari. Analisis neraca massa dan volume menggunakan softwareÃ‚Â STAN mengindikasikan bahwa metode teoritik cukup representatif, sedangkan perhitungan dengan metode empirik cenderung menjadi over-estimasi.Kata kunci: lumpur alum, kualitas lumpur, timbulan lumpur, instalasi pengolahan air, studi kasus